Malaysia and India’s Look East Policy (LEP) : hand in hand towards greater cooperation / Suseela Devi Chandran - Chandran, Suseela Devi (Universiti Teknologi MARA, Shah Alam, 2014)
It has been two decades since India launched its much-vaunted ‘Look East Policy’ (LEP). However, given the 20 years of India’s LEP, Malaysia perceives that India’s LEP lacks “robustness”. India may claim its success of LEP by it engagement with countries in the Southeast Asia region. However, the success of LEP towards each individual country varies. The recent conclusion of free trade agreements between Malaysia and India called Comprehensive Economic Cooperation Agreement (CECA) on February 2011 under the umbrella of Strategic Partnership provided new opportunities for economic collaboration. The two countries presently are moving forward to materialize the ‘Strategic Partnership’ that was established in October 2010. This ‘strategic partnership’ meant building stronger bilateral ties and re-engagement in areas such as the economy, security-defence, and sociocultural dimensions. This paper focuses on Malaysia’s perspective on India’s LEP and how Malaysia and India are working together through this strategic partnership. This paper is divided into four parts: First, an overall perspective on Malaysia-India relations is discussed briefly mainly from economic, defence and socio cultural areas. Second, it examines India’s LEP from Malaysia’s perspective. Third, the paper provides some recommendation on how Malaysia and India can work together. Fourth, the paper concludes by stating that the Malaysia-India bilateral relations could move on beyond the traditionally historical and cultural linkages to a higher level of strategic partnership.